Systematic Literature Review on Green IT Practice and Executional Factors - Sri Fatiany Abdul Kader Jailani; Lili Marziana Abdullah (International Journal of Supply Chain Management, 2017)
Green ICT practice is immediately turning into a key business component for many organisations. Thus, this study aims to examine Green IT practice research in the literature. At the same, time this study emphasises that the practice of implementing Green IT can be applied by any organisation. For that purpose, a Systematic Literature Review (SLR) method is used in which 57 out of 150 studies meet the search criteria. From that number 18 studies focus on Green IT practice. Based on the analysis of the studies, 17 factors are identified as motivators for organisations to apply Green IT practice. Therefore, this paper will be a useful guide for organisations to bring in greener technologies in the application of Information Technology.